2017
DOI: 10.1111/soc4.12489
|View full text |Cite
|
Sign up to set email alerts
|

Social movement coalitions: Formation, longevity, and success

Abstract: Social movements rely on coalitions to help mobilize the mass numbers of people necessary for success. In this article, we review the literature on social movement coalition formation, longevity, and success. We identify five factors critical to coalition formation: (a) social ties; (b) conducive organizational structures; (c) ideology, culture, and identity; (d) the institutional environment; and (e) resources. Next, we explore the extent to which coalition survival is influenced by these same factors and arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 113 publications
(171 reference statements)
2
61
0
Order By: Relevance
“…Among other things, this will require consideration of what type of coalition one is studying given some of the varying challenges they are likely to face. For instance, is it an event coalition or a longer‐term alliance (Van Dyke & Amos, )? And is the coalition, within‐movement, cross‐movement, identity group based, pan‐ethnic, intersectional, and/or a state actor–social movement coalition (Brooker & Meyer, )?…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among other things, this will require consideration of what type of coalition one is studying given some of the varying challenges they are likely to face. For instance, is it an event coalition or a longer‐term alliance (Van Dyke & Amos, )? And is the coalition, within‐movement, cross‐movement, identity group based, pan‐ethnic, intersectional, and/or a state actor–social movement coalition (Brooker & Meyer, )?…”
Section: Resultsmentioning
confidence: 99%
“…Crucially, such alliances are able to put more pressure on targets and enhance political leverage (Almeida, ; Staggenborg, ). Perhaps not surprisingly then, coalitions are associated with increased rates of success (Beamish & Luebbers, ; Gamson, ; Van Dyke & Amos, ). Broad coalitions have been recognized as particularly important given their advantage in mobilizing larger numbers of people and enabling the employment of tactics across greater geographic space, which can further increase the chances for movement success (Almeida, , ; Gelb & Shogan, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, pre-existing features of the policy environment, such as norms, may create opportunities for effective framing that will resonate with policymakers (Shiffman et al, 2016a: i9). I also note that the research on the transnational women's movement and social movement coalitions has also highlighted the significance of some of these variables, including leadership (Moghadam, 2005: 98;Van Dyke & Amos, 2017), organizational structure, and governance (Moghadam, 2005: 99-102;Van Dyke & Amos, 2017). Moreover, much like the GHAPP, previous research on social movement coalitions has also demonstrated that factors internal to a coalition as well as features of a coalition's external environment explain coalition formation, longevity, and outcomes (Van Dyke & Amos, 2017).…”
Section: Policy Environmentmentioning
confidence: 98%
“…Scholars have also found that religious clubs/organizations and churches also bring immigrant communities from different ethnic groups together and reinforce panethnic identities among group members (Lopez & Espiritu, ; Okamoto & Mora, ; Ricourt & Danta, ). Such processes facilitate multi‐group coalitions (Van Dyke & Amos, ) and immigrant mobilization. Indeed, on the eve of the massive 2006 demonstrations for immigrant rights, the U.S. Conference of Catholic Bishops organized a “Justice for Immigrants” campaign that was coordinated nationally through dioceses and parishes (Heredia, ).…”
Section: Emergencementioning
confidence: 99%